2006
DOI: 10.1111/j.1365-2249.2006.03033.x
|View full text |Cite
|
Sign up to set email alerts
|

IA-2 antibody isotypes and epitope specificity during the prediabetic process in children with HLA-conferred susceptibility to type I diabetes

Abstract: SummaryThe natural history of preclinical diabetes is partly characterized, but there is still limited information on the dynamics of the immune response to β β β β -cell autoantigens during the course of preclinical disease. The aim of this work was to assess the maturation of the humoral immune response to the protein tyrosine phosphatase(PTP)-related proteins (IA-2 and IA-2β β β β ) in preclinical type I diabetes (TID). Forty-five children participating in the Finnish Type I Diabetes Prediction and Preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…In the DIPP study, we explored the maturation of the humoral immune response to IA‐2 and IA‐2β. We observed that the children who progressed to clinical T1D tended to have an initial JM‐specific response more often, and such a response was more frequently dominant during the observation period when compared to the non‐progressors .…”
Section: Epitope‐specific Autoantibodiesmentioning
confidence: 78%
See 1 more Smart Citation
“…In the DIPP study, we explored the maturation of the humoral immune response to IA‐2 and IA‐2β. We observed that the children who progressed to clinical T1D tended to have an initial JM‐specific response more often, and such a response was more frequently dominant during the observation period when compared to the non‐progressors .…”
Section: Epitope‐specific Autoantibodiesmentioning
confidence: 78%
“…We have studied the isotype response to IA‐2 in 45 DIPP children, out of whom 15 developed T1D during their follow‐up. The children, who remained non‐diabetic had IgE subclass IA‐2A more frequently and higher integrated levels of IgE‐IA‐2A than the progressors (Table ) .…”
Section: Isotype‐specific Autoantibodiesmentioning
confidence: 99%
“…For instance, a difference in IAA affinity has been observed between individuals with low or high risk of disease progression, while this was not the case for IA2A where antibody titers rather than affinity had higher relevance for risk stratification . Making use of antibody properties might however not be uncomplicated, because even though IA2A affinity was not related to disease progression, IA2A epitope specificity has been shown to differ between those who developed diabetes or not . Progression to T1D has also been related to IA2A epitope spreading .…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in the age at diagnosis between those positive for IgE subclass IA-2A and the negative ones. One would have expected IgE-positive children to be older at the time of diagnosis based on our earlier observation that an IgE class IA-2 response protects from progression to T1D among IA-2A-positive children (17,20).…”
Section: Discussionmentioning
confidence: 99%
“…For example, IgG4 subclass IA-2A (21) as well as IgE class IA-2A (17,20) have been associated with protection from progression to T1D. JM-specific IA-2A have been shown to be one of the first epitope-specific IA-2A to appear in young children (9), and they have been associated with a greater risk of progression to overt T1D (9,17,20). There are, however, fewer studies measuring the same parameters among patients with newly diagnosed T1D.…”
Section: Discussionmentioning
confidence: 99%